SMAD7 variant rs4939827 is associated with colorectal cancer risk in Croatian population. - ZGAGA, LINA (My University, 2013)
Background Twenty common genetic variants have been associated with risk of developing colorectal cancer (CRC) in genome wide association studies to date. Since large differences between populations exist, generalisability of findings to any specific population needs to be confirmed. Aim The aim of this study was to perform an association study between risk variants: rs10795668, rs16892766, rs3802842 and rs4939827 and CRC risk in Croatian population. Methods An association study was performed on 320 colorectal cancer cases and 594 controls recruited in Croatia. We genotyped four variants previously associated with CRC: rs10795668, rs16892766, rs3802842 and rs4939827. Results SMAD7 variant rs4939827 (18q21.1) was significantly associated with CRC risk in Croatian population. C allele was associated with a decreased risk, odds ratio (OR): 0.70 (95% CI: 0.57-0.85, P=3.5E-04). Compared to TT homozygotes, risk was reduced by 34% in heterozygotes (OR=0.66, 95% CI: 0.47-0.92) and by 52% in CC homozygotes (OR=0.48, 95% CI: 0.33-0.72). Conclusion Our results show association of rs4939827 with colorectal cancer risk in Croatian population. The higher strength of the association in comparison to other studies suggests population-specific environmental or genetic factors may be modifying the association. More studies are needed to further describe role of rs4939827 in CRC. Likely reason for failure of replication for other 3 loci is inadequate study power.
PUBLISHED
Keywords: Colorectal cancer; Croatia